The nature-based school curriculum: A solution to learning-teaching that promotes students’ freedom - Supriyoko Supriyoko; Ana Fitrotun Nisa; Novita Freshka Uktolseja (LPMPP Universitas Negeri Yogyakarta, 2022)
This research aims to describe the nature-based school curriculum as a solution to the learning-teaching that promotes students’ freedom. The implementation of the learning-teaching is designed to be fun based on the natural characteristics of children. This research utilized a qualitative-descriptive method involving students, teachers, and parents as participants. Data were collected through observations, questionnaires, and interviews. The data analysis consisted of four stages: data collection, data reduction, data presentation and drawing conclusions. The results of this research indicate that the curriculum developed at the nature-based school is implemented by integrating the national curriculum with the natural school curriculum consisting of four pillars: morality, scientific logic, leadership, and entrepreneurship. The positive impact of this research is that the innovation of natural curriculum has been in line with the implementation of independent curriculum by implementing four pillars in learning-teaching process and are carried out through experience-based learning and project-based learning methods. Students are facilitated to express their opinions in different activities and are given the freedom to choose a place to learn in several activities. For example, in some activities, students are free to choose learning places which can be in the prayer room, in the school yard, in the library, or in other places. The learning-teaching can increase students’ enthusiasm to go to school, be happy, feel valued and feel free when they are at schools. With this nature-based school curriculum, children develop according to their nature and grow into meaningful, independent, and beneficial human beings in the surrounding environment who have noble character, have logical abilities, have a good leadership spirit, and have an entrepreneurial spirit.